Markers with low GenTrain scores can generate spurious signals in genome‐wide scans for transmission ratio distortion. (29th June 2021) - Luigi‐Sierra, María Gracia; Casellas, Joaquim; Martínez, Amparo; Vicente Delgado, Juan; Fernández Álvarez, Javier; Such, Francesc Xavier; Jordana, Jordi; Amills, Marcel
Summary: Transmission ratio distortion (TRD) is the preferential transmission of one specific allele to offspring at the expense of the other. The existence of TRD is mostly explained by the segregation of genetic variants with deleterious effects on the developmental processes that go from the formation of gametes to fecundation and birth. A few years ago, a statistical methodology was implemented in order to detect TRD signals on a genome‐wide scale as a first step toward uncovering the biological basis of TRD and reproductive success in domestic species. In the current work, we have analyzed the impact of SNP calling quality on the detection of TRD signals in a population of Murciano–Granadina goats. Seventeen bucks and their offspring ( N  = 288) were typed with the Goat SNP50 BeadChip, whereas the genotypes of the dams were lacking. Performance of a genome‐wide scan revealed the existence of 36 SNPs showing significant evidence of TRD. When we calculated GenTrain scores for each of the SNPs, we observed that 25 SNPs showed scores below 0.8. The allele frequencies of these SNPs in the offspring were not correlated with the allele frequencies estimated in the dams with statistical methods, providing evidence that flawed SNP calling quality might lead to the detection of spurious TRD signals. We conclude that, when performing TRD scans, the GenTrain scores of markers should be taken into account to discriminate SNPs that are truly under TRD from those yielding spurious signals owing to technical problems.